Neutrophil infiltration and myocarditis in patients with severe COVID-19: A post-mortem study - Zhang, Quanyu; Zhang, Huarong; Yan, Xiaowei; Ma, Sicong; Yao, Xiaohong; Shi, Yu; Ping, Yifang; Cao, Mianfu; Peng, Chengfei; Wang, Shuai; Luo, Min; Yan, Chenghui; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: To investigate cardiac pathology in critically ill coronavirus disease 2019 (COVID-19) patients and identify associations between pathological changes and clinical characteristics. Methods: The present autopsy cohort study included hearts from 26 deceased patients hospitalized in intensive care units due to COVID-19, and was conducted at four sites in Wuhan, China. Cases were divided into a neutrophil-infiltration group and a no-neutrophil group based on the presence or absence of histopathologically identified neutrophilic infiltrates. Results: Among the 26 patients, histopathological examination identified active myocarditis in 4. All patients with myocarditis exhibited extensive accompanying neutrophil infiltration, and all patients without myocarditis did not. The neutrophil-infiltration group exhibited significantly higher rates of detection of interleukin 6 (100% vs. 4.6%) and tumor necrosis factor alpha (100% vs. 31.8%) than the no-neutrophil group (both p < 0.05). On admission the 4 patients with neutrophil infiltration in myocardium had significantly higher baseline levels of aspartate aminotransferase, D dimer, and high sensitivity C reactive protein than the other 22 patients (all p < 0.05). During hospitalization patients with neutrophil infiltration had significantly higher maximum creatine kinase-MB (median 280.0 IU/L vs. 38.7 IU/L, p = 0.04), and higher troponin I (median 1.112 ng/mL vs. 0.220 ng/mL, p = 0.56) than patients without neutrophil infiltration. Conclusion: In hearts from deceased patients with severe COVID-19, active myocarditis was commonly accompanied by neutrophil infiltration. Patients with neutrophil-infiltrated myocarditis had a series of severely abnormal laboratory test results on admission, and high maximum creatine kinase-MB during hospitalization. The role of neutrophils in severe heart injury and systemic condition in patients with COVID-19 should be emphasized.